Isocaloric low protein diet in a mouse model for vanishing white matter does not impact ISR deregulation in brain, but reveals ISR deregulation in liver. (3rd June 2022) - Wisse, Lisanne E.; Visser, Denise; ter Braak, Timo J.; Bakkali, Abdellatif; Struys, Eduard A.; Morrison, Christopher D.; van der Knaap, Marjo S.; Abbink, Truus E. M.
ABSTRACT: Objective: Vanishing white matter (VWM) is a genetic brain white matter disorder caused by mutations in eIF2B. eIF2B is central in the integrated stress response (ISR), during which its activity is inhibited by various cellular stresses. VWM is a chronic progressive disease with episodes of rapid neurological deterioration provoked by stresses. VWM patients and VWM mouse models show ISR deregulation in brain, correlating with chronic disease development. ISR inhibition ameliorates the chronic disease in VWM mice. The subacute deteriorations have not been modeled yet. We hypothesized that ISR activation could worsen disease progression in mice and model the episodic neurological deterioration. Method: We chose to activate the ISR by subjecting wild-type (wt) and VWM mice to an isocaloric low protein diet. This model would allow us to investigate the contribution of ISR activation in subacute decline in VWM. Results: We found that the low protein diet did not significantly affect amino acid levels nor ISR levels in wt and VWM mouse brain. Our study serendipitously led to the discovery of increased levels of glycine, asparagine and Fgf21 mRNA in VWM mouse brain irrespective of the dietary protein content. Strikingly, the ISR was not activated by the low protein diet in the liver of VWM in contrast to wt mice, due to a modest ISR deregulation in this organ. Discussion: A model for subacute neurological deterioration in VWM was not established. Possibly, ISR deregulation in VWM results in reduced ISR responsiveness.